Pengaruh Motivasi, Komitmen, dan Kompetensi Terhadap Prestasi Kerja Karyawan - Ahmad Rojikun (Prisani Cendekia, 2022)
This research was conducted on employees at the XYZ Clinic in Depok. The research method used in this study was descriptive and verification methods. The sample used was 48 employees with purposive sampling method. The data analysis technique used is multiple regression with SPSS 26 software. The results show that motivation has a positive and significant effect on work performance, and commitment has a positive and significant effect on work performance, competence has a positive and significant effect on work performance. Motivation, Commitment and Competence have a simultaneous effect on work performance.